Loss and reinduction of desiccation tolerance in millet seeds - Fernandes, Joana Souza (2018)
Desiccation is the most severe form of water stress, and in orthodox seeds the desiccation tolerance is acquired during maturation, lost during or shortly after visible germination. This trait can be reestablished at the moment of desiccation sensitivity, leading to a b etter understanding of recalcitrance and tolerance to abiotic stresses during the seed germination. In this research, physiological aspects related to the loss of desiccation tolerance were evaluated through the expression of the enzymes superoxide dismutase, catalase, peroxidase and α-amylase, and also the expression of heat -resistant proteins at the points determined in assays for characterization of desiccation tolerance loss: 0h, 3h, seeds with 1mm and 3mm of radicle. Several protocols were tested for the desiccation tolerance re-induction, and the analysis of the sugar content, the expression of genes related to heat resistant proteins, and the general quantification of this proteins, was done in radicle and aerial part of seeds after 18 hours of imbibi tion in germinated seeds dried under 30 and 50% relative humidity at 22 °C for 72 hours (MADT). Millet seeds lost desiccation tolerance when the radicle reached 1 mm in length. According to the enzymatic standards, peroxidase and α -amylase enzymes, as well as the activity of heat -resistant proteins, were related to loss of tolerance to desiccation in millet seeds. In the re-induction of desiccation tolerance, raffinose accumulation, stachyose and fructose were observed in radicles submitted to MADT 50% RH t reatment, with a probable correlation with the dessication tolerance reinduction. The analyzed genes, PgLEA (member of family 7); PgDHN (dehydrin, family member 2) and PgHsp10 (chaperone chassis as Hsp10), showed no correlation with the treatments, as well as analysis of the general expression of heat-resistant proteins, which even present, were not significantly altered with the application of treatments of desiccation tolerance reinduction studied.